Research for the Working Theorem and Application of Electrocardiogram - Takada, Mai (Transactions on Computer Science and Intelligent Systems Research, 2024)
Electrocardiograms (ECGs) are essential for diagnosing cardiac diseases, and recording the heart’s electrical activity across cycles. Despite their critical role, there remains a gap in understanding the detailed principles and historical development of ECGs. This article introduces the historical development, basic principles, and application of ECG in the diagnosis of heart diseases. The working principle of ECG is studied, including the depolarization and repolarization process of myocardial cells, and how these physiological activities are manifested in ECG waveforms. The research involves analyzing the process of depolarization and repolarization in cardiomyocytes, illustrating how these principles manifest in ECG waveforms. The findings show that ECGs provide valuable insights into cardiac function, enabling the detection of arrhythmias and other conditions. This study concludes that ECGs are indispensable for cardiac diagnostics and highlights their continued significance in modern medicine. This study provides an in-depth exploration of ECG technology and its application in the diagnosis of heart disease, laying an important foundation for future research and practice.